2014
DOI: 10.1016/j.cell.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Adipsin Is an Adipokine that Improves β Cell Function in Diabetes

Abstract: Summary A hallmark of type 2 diabetes mellitus (T2DM) is the development of pancreatic β cell failure, resulting in insulinopenia and hyperglycemia. We show that the adipokine adipsin has a beneficial role in maintaining β cell function. Animals genetically lacking adipsin have glucose intolerance due to insulinopenia; isolated islets from these mice have reduced glucose-stimulated insulin secretion. Replenishment of adipsin to diabetic mice treated hyperglycemia by boosting insulin secretion. We identify C3a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
333
7
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(374 citation statements)
references
References 63 publications
(69 reference statements)
28
333
7
6
Order By: Relevance
“…Previous studies, however, did not demonstrate any relation to CVD outcomes 10, 21. Adipsin has been shown to regulate inflammation in adipose tissue and may improve beta‐cell function in diabetes mellitus 11, 23, 24. Among women, adipsin is correlated with metabolic parameters, including body mass index, insulin resistance, and carotid atherosclerosis,3, 12, 25 but it has not been linked to adverse CVD outcomes previously.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies, however, did not demonstrate any relation to CVD outcomes 10, 21. Adipsin has been shown to regulate inflammation in adipose tissue and may improve beta‐cell function in diabetes mellitus 11, 23, 24. Among women, adipsin is correlated with metabolic parameters, including body mass index, insulin resistance, and carotid atherosclerosis,3, 12, 25 but it has not been linked to adverse CVD outcomes previously.…”
Section: Discussionmentioning
confidence: 97%
“…Most recently, experimental and clinical studies suggest that novel adipokines such as adipsin and visfatin might have an energetic role in the cascade of the events leading to diabetes mellitus. Namely, adipsin has a beneficial role in maintaining β cell function and visfatin plays an important role in glucose metabolism (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In adipsin -/-mice, Lo et al showed that this protein plays an important role in insulin secretion by the pancreatic β-cells. They also showed that adipsin is decreased in patients with T2D and β-cell failure [110]. The data by Lo et al suggest that adipsin stimulates insulin secretion via actions of C3a on its receptor to improve glucose homeostasis in vivo.…”
Section: Further Adipokinesmentioning
confidence: 80%